A comparative study of the effect of clay and titanium dioxide on the mechanical properties and permeability of nanocoated cotton fabrics. Issue 1 (25th August 2017) - Glouia, Yosra; Dhouib, Soufien; Abid, Khaled
ABSTRACT: This paper explores a comparison of mechanical properties of nanocoated cotton fabric for coatings synthesized with two different additives: Tunisian natural clay and titanium dioxide. The natural raw clay is a mixture of various other simple clays (kaolinite, calcite, illite, and quartz) requires preparation. TiO2 and Tunisian clay were added to two different resins, polyacrylate and polyurethane, widely used for numerous textile improvements such as impermeability and brightness effects. The additives used offer the advantage of being nontoxic and widely available. First, we check the constitution of the nanocoatings via X‐ray diffraction. Then, a defined amount of the resulting solution is applied on a cotton fabric. Finally, we check the mechanical properties and barrier effects on the modified fabric. The results show that when a small amount of clay or TiO2 particles are added to resin, the tear, tensile, bursting, and abrasion strength and water and air barrier properties of the coated fabric are globally enhanced. However, the use of natural clay in the coating gives better results than TiO2 . In fact, in terms of mechanical performance, it is two to nine times more efficient than the titanium dioxide coating, except for the barrier effect, which is exactly two times more efficient. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45642. Abstract :